Effects of rancidity in choice white grease on growth performance and nutrient digestibility in weanling pigs - Robert H Hines; H Cao; C A Maloney; D W Dean; D J Lee; J S Park; Joel M DeRouchey; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 2000)
Our data suggest that adding slightly rancid choice white grease with peroxide values of 40 mEq/kg and less and p-anisidine values of 10.6 and less to diets will not decrease growth performance in nursery pigs. However, reduced feed intake and, thus, reduced rate of gain occurred at greater peroxide and panisidine values.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Pigs; Fat quality; Rancidity